Book-use study at the Pampanga Provincial Library and Information Center - Mendoza, Mary Joie Q.; Sison, Josephine C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
It is a must for every library to conduct collection evaluation in order to be able to determine whether its collection is meeting its objectives. It is for this reason that this study was conducted. This study was primarily focused on book-use at the Pampanga Provincial Library and Information Center. It relied heavily on circulation statistics to determine the extent of use in the library.
Furthermore, this study intended to determine the effect of the characteristics such as subject class, publication date, physical condition and language on the usage of books. Ten percent of each of the four categories, i. e. Non-fiction Books by Filipino Authors, Non-fiction Books by Foreign Authors, Kapampangan Collection and Rizaliana Collection, were selected using systematic random sampling.
The findings revealed that among the four characteristics, which affect book use, only the subject class, as indicated by the category to which the books belong, seemed to affect the book usage pattern in the Pampanga Provincial Library and Information Center. The other three factors (publication date, physical condition and language) were found to be unreliable in determining the extent of use of the books because the percentage of use in these three factors were evenly distributed. The even distribution of book use suggests that these factors do not affect why the books are borrowed.
Undergraduate thesis (B.L.I.S.)--University of the Philippines, Diliman.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Pampanga Provincial Library and Information Center; Public libraries -- Evaluation. -- Philippines -- Pampanga